Parathyroid near-infrared autofluorescence differently benefits depending on the surgeon’s skill for preventing from hypoparathyroidism after total thyroidectomy: A systematic review and meta-analysis - Takeshi Takahashi; Shalyn J. D. Sa; Ryohei Oya; Shusuke Ohshima; Jo Omata; Yusuke Yokoyama; Ryusuke Shodo; Yushi Ueki; Yukinori Takenaka; Hidenori Inohara; Arata Horii (PLoS ONE, 2025)
Objective To evaluate the role of parathyroid near-infrared autofluorescence in reducing the incidence of postoperative hypocalcemia and hypoparathyroidism after total thyroidectomy, and to determine which surgeons benefit most from parathyroid near-infrared autofluorescence use. Methods A literature search was conducted in PubMed, Web of Science, and the Cochrane Library databases for English-language articles published from June 2011 to October 31, 2023. The inclusion criteria were studies conducted on patients who underwent total thyroidectomy for benign or malignant thyroid pathologies, comparing postoperative parathyroid function between parathyroid near-infrared autofluorescence techniques and conventional surgery with data on calcium and/or parathyroid hormone levels. The exclusion criteria included: reviews, letters, meta-analyses, case reports, animal experiments, or basic research. Of the initial 387 articles retrieved, we included 14. A meta-analysis was performed to calculate the pooled odds ratio and weighted mean deviation with a random-effects model. Main outcomes were Calcium and parathyroid hormone levels after total thyroidectomy with or without parathyroid near-infrared autofluorescence use. Results Fourteen studies were included in the meta-analysis. Pooled odds ratios of temporary and permanent hypocalcemia were 0.56 (95% confidence interval 0.43–0.72) and 0.61 (95% confidence interval 0.33–1.13), respectively. Meta-regression analysis revealed that near-infrared autofluorescence benefits surgeons with the high incidence of temporary hypocalcemia by naked eye surgery (≥15%) by reducing temporary hypocalcemia (p = 0.0091) and skillful surgeons by increasing the number of autotransplanted parathyroid glands (p = 0.0225). Conclusions Parathyroid near-infrared autofluorescence has different benefits depending on the skill level of the surgeon.